The Interrelationship between Culture, Law and Peace: Connections and Frictions - Weber, Helmut (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Abstract: The text explores the connections and tensions between culture, law, and peace. It contemplates culture’s relationship with law, ranging from ’high culture’ as art to broader definitions of culture as all things made by humans. The author defines culture as extra-legal norms. While many cultural norms don’t clash with law, conflicts emerge where they coincide but differ. The text examines instances of conflicts between legal and cultural norms and their resolutions, focusing on German legal and cultural developments. The author offers examples that demonstrate how conflicts between law and culture can be resolved through legislative changes, external influences, and gradual shifts in societal attitudes. The author concludes that peace prevails where legal and cultural rules align.